The Impact of Multimedia-enhanced STEAM Activities on Foreign Language Learners' Development of Oracy Skills and Willingness to Communicate - Zeinab Hatami Nasab; Rahimi, Mehrak (Bulletin of education and research, 2023)
The study explored the impact of multimedia-enhanced STEAM activities on English as a foreign language (EFL) learners' development of oracy skills and willingness to communicate (WTC) in an online course. The sample included 42EFL learners who were randomly split into two groups with 21 students in each. Before the study, both groups' listening and speaking proficiency was assessed by the listening and speaking modules of the IELTS test. Also, the WTC questionnaire was utilized to evaluate their WTC in English before the study. The experimental group received multimedia-enhanced instruction where the concepts of each domain of STEAM were taught by multimedia clips along the course. Meanwhile, the content was taught to the control group by conventional teaching materials of the textbook. The instruction was online and lasted for five months. Both groups' oral proficiency and WTC were assessed again after the study. One-way Multivariate Analysis of Variance method was used to analyze the collected data. The outcomes displayed a significant difference between the oral skills of the two groups and a non significant difference between their WTC after the treatment in favor of the experimental group. The practical significance of the results can be found in the tremendous potential of integrating STEAM curriculum with language teaching, particularly in technology-enhanced learning environments, for promoting students' interest in STEAM professions in countries like Iran that have a crisis in educating STEAM specialists. Follow-up studies on combining STEAM topics with teaching other subject matters using emerging technologies across different levels of education are recommended.